1979
DOI: 10.1002/jctb.503290703
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phosphate ions by collodion‐coated alumina

Abstract: The kinetics and the equilibrium adsorption of phosphate by collodion-coated alumina granules were investigated. Collodion-coated alumina can serve as a sorbent for phosphates in the treatment of hyperphosphatemic patients by haemoperfusion. The collodion coating lowers the surface area available for adsorption. The kinetics of adsorption were investigated by experiments in which the initial phosphate concentration, the quantity of sorbent and the grain size of sorbent were varied. The rate of adsorption is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(78 citation statements)
references
References 5 publications
3
69
0
Order By: Relevance
“…Basing on analysis of the Bangham plots (Aharoni et al 1979) it is possible to identify a sorption mechanism (see Supplementary material, Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Basing on analysis of the Bangham plots (Aharoni et al 1979) it is possible to identify a sorption mechanism (see Supplementary material, Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Bangham's equation (Aharoni et al, 1979) is represented as: 0 0 0 t C km log log log log(t) C q m 2.303V…”
Section: Bangham's Equationmentioning
confidence: 99%
“…It is found that the shaking temperature increased the value of α decreased while k o increased with the raise in temperature showing the adsorption of dye in pores of carbon is well controlled process [26,27]. Yaneva studied the experimental kinetic results were analyzed by series of rate/mass transfer equations.…”
Section: Elovich Modelmentioning
confidence: 99%